VD_FINDINFO Décision / 2013 / 822 vom 13. September 2013 - VD Tribunal cantonal (2013)
DÉFAUTCONTUMACE, PLAINTE PÉNALE, RETRAITVOIE DE DROIT, CLASSEMENT DE LA PROCÉDURE | 205 CPP (CH), 316 al. 1 CPP (CH), 319 CPP (CH)